1994
DOI: 10.1021/bi00196a003
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional solution structure and 13C assignments of barstar using nuclear magnetic resonance spectroscopy

Abstract: We present the high-resolution solution structure and 13C assignments of wild-type barstar, an 89 amino acid residue polypeptide inhibitor of barnase, derived from heteronuclear NMR techniques. These were obtained from measurements on unlabeled, uniformly 15N- and 13C/15N-labeled, and 10% 13C-labeled barstar samples that have both cysteines (at positions 40 and 82) fully reduced. In total, 30 structures were calculated by hybrid distance geometry-dynamical simulated annealing calculations. The atomic rms distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
151
1
1

Year Published

1995
1995
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(160 citation statements)
references
References 39 publications
7
151
1
1
Order By: Relevance
“…The C82A mutant of barstar has activity (3) and thermal stability similar to those of wt barstar (21) with a ∆G°(25°C) of 25 kJ mol -1 and is marginally destabilized to GuHCl denaturation (18) compared to wt barstar. The C82A structure shows significant differences from the solution structure of the protein reported previously (7,22). † 1 Abbreviations: C82A, crystal structure of the Cys82Ala mutant of barstar at 2.8 Å solved in this study; C40A:C82A, barstar double mutant; wt, wild-type barstar; rmsd, root-mean-square deviation; B-factor, crystallographic temperature factor; MC, main chain; SC, side chain; SA, simulated annealing; 1BTA, the uncomplexed NMR structure (7); 1BGS, 2.6 Å structure of barstar C40A:C82A complexed to barnase (9); 1BRS, identical to 1BGS except at a higher resolution of 2.0 Å (8); OS, occluded surface; ∆C p, change in excess heat capacity upon unfolding; DTNB, 5,5′-dithiobis(2-nitrobenzoic acid); TNB, 5-thio-2-nitrobenzoic acid; GuHCl, guanidine hydrochloride.…”
contrasting
confidence: 68%
See 1 more Smart Citation
“…The C82A mutant of barstar has activity (3) and thermal stability similar to those of wt barstar (21) with a ∆G°(25°C) of 25 kJ mol -1 and is marginally destabilized to GuHCl denaturation (18) compared to wt barstar. The C82A structure shows significant differences from the solution structure of the protein reported previously (7,22). † 1 Abbreviations: C82A, crystal structure of the Cys82Ala mutant of barstar at 2.8 Å solved in this study; C40A:C82A, barstar double mutant; wt, wild-type barstar; rmsd, root-mean-square deviation; B-factor, crystallographic temperature factor; MC, main chain; SC, side chain; SA, simulated annealing; 1BTA, the uncomplexed NMR structure (7); 1BGS, 2.6 Å structure of barstar C40A:C82A complexed to barnase (9); 1BRS, identical to 1BGS except at a higher resolution of 2.0 Å (8); OS, occluded surface; ∆C p, change in excess heat capacity upon unfolding; DTNB, 5,5′-dithiobis(2-nitrobenzoic acid); TNB, 5-thio-2-nitrobenzoic acid; GuHCl, guanidine hydrochloride.…”
contrasting
confidence: 68%
“…The NMR structure of free barstar had indicated that there were significant differences in the structures of the bound and free states (7,8,22). These differences were of three types: local changes in the conformations of residues in the binding region, an overall movement of the binding loop away from barnase, and global inward movements of the four helices in going from the bound to the free state.…”
Section: Resultsmentioning
confidence: 99%
“…The structure of barstar (21), the inhibitor of the ribonuclease barnase from Bacillus amyloliquefaciens, has been solved by NMR spectroscopy in solution (22), and the gross features of its folding pathway have been determined by rapid mixing methods and equilibrium thermodynamics (23). The active barstar mutant C40A/C82A/P27A (pseudo-wild-type barstar), which was used in this study, contains no cysteines which may give rise to crosslinks in the denatured state and only one proline residue.…”
mentioning
confidence: 99%
“…The majority of Barstar's residues are involved in secondary structure, and there is one extended loop between the first two helices which is used for binding with barnase. 15 conformation that has been shown to also be capable of inhibiting barnase activity. 18 Other reports show that there exist intermediates that are 'fast-refolding' unfolded states that differ from 'slow-refolding' unfolded states by cis and trans conformations, respectively, of the Tyr47-Pro48 bond.…”
Section: This Studymentioning
confidence: 99%